Optimalisasi Budaya Organisasi Dalam Upaya Meningkatkan Kinerja - Ony Devita Sintyasari; Rahayu Puji Suci; Adya Hermawati (Universitas Musamus,Merauke,Papua, 2021)
The purpose of this paper is to obtain empirical evidence of personality abilities and work motivation in encouraging the improvement of organizational culture and organizational performance, so besides obtaining empirical evidence it is necessary to increase the mediating ability of organizational culture. The writing uses quantitative methods, and the method used is the SEM-PLS program. Data were obtained through questionnaires distributed to 100 employees of KPP Pratama Bitung. Empirical evidence obtained in the form of personality and high motivation and able to encourage increased strengthening of organizational culture and organizational performance. In addition, it was also found that organizational culture is able to act as a strong mediation. Accurate and careful work results in the attention to detail indicator, obeying regulations even though they are not monitored in the aggressiveness indicator, and employee careers are considered by the organization in the stability indicator are items from each indicator that strongly support the creation of a strong organizational culture at KPP Pratama Bitung. This finding is supported by descriptive statistics the four research variables that get respondents' responses are high on average, characterized by sympathy for others, fluid and non-rigid working relationships, obeying the rules even though they are not supervised, as well as the percentage of realized tax revenues.